Pengaruh Penggunaan QField for QGIS dengan Model Team Assisted Individualization terhadap Kreativitas dan Hasil Belajar Siswa pada Materi Dasar-Dasar Pemetaan di SMAN 6 Solok Selatan - Azzahra, Sukma; Mariya, Sri (Lembaga Yasin AlSys, 2025)
The limited implementation of mobile-based geospatial technology in Geography education forms the background of this study, despite its significant potential to enhance students' creativity and learning outcomes. This research aims to (1) analyze the effect of using QField for QGIS integrated with the Team Assisted Individualization (TAI) model on students' creativity, and (2) describe its impact on learning outcomes in the topic of basic mapping at SMAN 6 Solok Selatan. A quantitative approach was used with a quasi-experimental design. The sample was selected through purposive sampling, involving two classes—E2 as the experimental group and E4 as the control group. Data were collected through tests, questionnaires, observations, and documentation, and analyzed using normality and homogeneity tests, t-tests, and N-Gain calculations. The results indicate that integrating QField for QGIS with the TAI model significantly improves students' creativity (p < 0.05), shifting from the